The influence of a Tabata interval-training program using an aquatic underwater treadmill on various performance variables - Rebold, M. J.; Kobak, M. S.; Otterstetter, R. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate the effects of an 8-week aquatic treadmill running (ATM) Tabata interval-training program on various performance variables including body fat percentage, force production, flexibility, and anaerobic power. Totally, 25 participants (17 males and 8 females) were randomized into either a control group (CON), which only completed Pre- and Posttesting, or exercise group (EX), which took part in the 8-week ATM Tabata interval-training program. Pre- and Posttesting consisted of the following measurements: body fat percentage, flexibility, force production, and anaerobic power. The Tabata interval-training program consisted of sprinting on an ATM at 7.5 miles/h and with the front jets turned on at 80, 85, 90, and 95% progressively increasing throughout the 8 weeks. A 2-way repeated measures analysis of variance revealed a significant effect of time (F = 236.13; p < 0.001) and group by time interaction (F = 1.95; p = 0.02). Paired-samples t-test revealed a significant difference in the CON group from Pre- to Posttesting for mean power from the Wingate test (t = -2.20; p = 0.05) and a significant difference in the EX group for right leg goniometry (t = -2.34; p = 0.04) and mean power from the Wingate test (t = -2.81; p = 0.02). These results are favorable because it demonstrates that participants who engage in an ATM Tabata interval-training program can elicit a strong enough stimulus to improve flexibility and anaerobic power in terms of mean power while decreasing musculoskeletal impact placed on the ligaments, joints, and tendons